Consumer Preferences and Attitudes in Purchasing Cavendish Bananas of the “Sunpride” Brand at Lotte Mart Pakuwon Mall Surabaya (Fishbein Multiattribute Model Approach) - Ratnakanyaka, Meimy; Hendrarini, Hamidah; Tondang, Ika Sari (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
The growth of fresh fruit consumption in Indonesia, especially bananas, is influenced by public awareness of health and product quality. However, there is a problem in the form of a decline in banana consumption in the city of Surabaya during the period 2021–2024. This study aims to identify consumer characteristics and preferences for purchasing